Bioethics and Reason in a Secular Society: Reclaiming Christian Bioethics - Wildes, Kevin Wm. (Conatus - Journal of Philosophy, 2018)
Bioethics evolved from traditional physician ethics and theological ethics. It has become important in contemporary discussions of Medicine and ethics. But in contemporary secular societies the foundations of bioethics are minimal in their content and often rely on procedural ethics. The bioethics of particular communities, particularly religious communities, are richer than the procedural ethics of a secular society. Religious bioethics, situated within religious communities, are richer in content in general and in the lived reality.